2020
DOI: 10.1007/s00068-020-01515-w
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and predictors of traumatic spine injury in severely injured patients: implications for emergency procedures

Abstract: Purpose This study aimed to identify the prevalence and predictors of spinal injuries that are suitable for immobilization. Methods Retrospective cohort study drawing from the multi-center database of the TraumaRegister DGU®, spinal injury patients ≥ 16 years of age who scored ≥ 3 on the Abbreviated Injury Scale (AIS) between 2009 and 2016 were enrolled. Results The mean age of the 145,833 patients enrolled was 52.7 ± 21.1 years. The hospital mortality rate was 13.9%, and the mean injury severity score (IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
6
7
2
1
Order By: Relevance
“…Our study documents the important role of the cervical MRI study in patients with cervical spinal cord trauma, which is confirmed to be the gold standard for diagnosis, decision making process and prognosis. Moreover, the MRI study may be of value in cases with clinical and radiological mismatch [1]. In our experience patients with longer lesion length, relevant spinal cord compression and intramedullary hematoma documented by MRI study, could be surgically treated as soon as possible to achieve the best possible recovery [25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study documents the important role of the cervical MRI study in patients with cervical spinal cord trauma, which is confirmed to be the gold standard for diagnosis, decision making process and prognosis. Moreover, the MRI study may be of value in cases with clinical and radiological mismatch [1]. In our experience patients with longer lesion length, relevant spinal cord compression and intramedullary hematoma documented by MRI study, could be surgically treated as soon as possible to achieve the best possible recovery [25].…”
Section: Discussionmentioning
confidence: 93%
“…Cervical spinal cord injury (cSCI) is a devastating condition and a common cause of disability and death in young people [1,2]. Epidemiological studies documented that cSCI has an estimated incidence of 750 cases per million annually with a great impact upon families and society [3].…”
Section: Introductionmentioning
confidence: 99%
“…Außerdem sind HWS-Verletzungen bei bewusstlosen Patienten doppelt so häufig zu finden wie bei wachen Patienten. Ein Drittel aller polytraumatisierten Patienten hat Verletzungen der Wirbelsäule [4].…”
Section: Epidemiologieunclassified
“…It is necessary to maintain the cervical spinal cord in patients with traumatic head injuries to avoid secondary injuries [ 2 ]. According to available studies, 1–2% of individuals with head injuries also have spinal injuries [ 3 ]. Unlike other types of accidents, high rates of spinal injuries are reported in individuals involved in motor vehicle accidents [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Causes of injury may be associated with spinal injuries among individuals with traumatic head injuries [ 6 ]. Besides the type of accidents, other epidemiological characteristics like older age and degree of injuries are also associated with the prevalence of spinal injuries among individuals with traumatic head injuries [ 3 ]. Detection of spinal injuries among individuals with traumatic head injuries is necessary because spinal injuries lead to functional alterations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%